Brain mapping for lesions in primary motor cortex: integrated surgical approach. (12th October 2019) - Lavrador, José; Ghimire, Prajwal; Brogna, Christian; Furlanetti, Luciano; Patel, Sabina; Gullan, Richard; Ashkan, Keyoumars; Bhangoo, Ranjeev; Vergani, Francesco
Abstract: Background: Lesions within the corticospinal tract (CST) represent significant surgical challenge with a delicate functional trade-off that should be integrated in the overall patient-centred treatment plan. Methods: Patients with lesions within the CST with preoperative cortical and subcortical mapping (nTMS and tractography), intraoperative mapping and intraoperative provisional histological information (smear +- 5-ALA) were included. This independently acquired information was integrated in a decision-making process model to determine the intraoperative extent of resection. Results: 10 patients (6 patients with metastatic precentral tumour; 1 patient with Grade III and 2 patients with grade IV gliomas; 1 patient with precentral vascular malformation) were included in the study. Majority of the patient had pre-operative motor deficit (60%). 50% patients underwent gross total resection and 40% patients underwent near total resection of the lesions. In only one patient, no surgical resection was possible after both pre-operative and intraoperative mapping. 70% of patients remained stable postoperatively and 20% improved from previous motor weakness. Conclusion: The independently acquired anatomical (anatomical MRI) and functional (nTMS and tractography) in patients with CST lesions provide a more accurate guide for resection. The inclusion of the histological information (smear +- 5-ALA) further allows the surgical team to balance the potential functional risks within the global treatment plan. Therefore, the patient is kept at the centre of the informed decision making process.